The Baker Lake Printmaking Revival - Fisher, Kyra Vladykov (ARCTIC, 1997)
The history of printmaking in Baker Lake is also the history of a people going towards self-sufficiency and nationhood: "a culture employing art unconsciously for identity while moving inevitably into the unknown" (Bloore, 1973: Foreword). . [The author describes the conditions under which she moved to Baker Lake to set up the drawing and printmaking program for Nunavut Arctic College. This was the first time since the late 1980s that printmaking was going to be done there. After tracing the history of printmaking in Baker Lake, Fisher describes the problems faced by the artists in securing adequate space to pursue their work, problems of marketing, and the lamentable lack of tangible appreciation for the valuable contribution these artists provide towards the preservation of culture.]